Research Progress in the Treatment of Bronchiectasis by Traditional Chinese Medicine - Zhao, Tong; Li, Yaohui (Journal of Contemporary Medical Practice, 2025)
The incidence of bronchiectasis is associated with infection, immunodeficiency, heredity and so on. Because of its persistent and irreversible expansion, it often recurs and persists, which seriously affects the quality of life of patients. Modern medical treatment focuses on the control of acute exacerbation of infection, but it is still unable to cure it. In recent years, the research on the prevention and treatment of bronchiectasis by traditional Chinese medicine has gradually increased, and some studies have found that traditional Chinese medicine has certain advantages and characteristics in controlling infection in the acute phase, prolonging the stable phase, reducing the number of recurrences and acute exacerbations, and improving immunity. This article systematically summarizes the understanding of the pathogenesis and treatment ideas of bronchiectasis by doctors in the past five years, and provides reference for clinical treatment of this disease.